Investigation into the mechanical properties and metal creaks of a diesel locomotive wheel - Jastremskas, Virgilijus; Vaičiūnas, Gediminas; Černašėjus, Olegas; Rudzinskas, Vitalijus (Transport, 2010)
After JSC ‘Lithuanian Railways’ (AB ‘Lietuvos geležinkeliai‘) bought new Siemens ER20 CF locomotives produced in Western Europe and brought them into service, some of them have already done about 170–200 thousand km that caused the appearance of indentations of an inadmissible size (the depth is more than 3 mm, the length – 10 mm) the elimination of which turning cutting results in up to 20 mm loss of a wheel. Having grounded off the metal layer of indentation depth, indentation reappears (metal ‘flakes off’) and needs to be removed by returning cutting the wheel. The purpose of the current investigation is to determine whether there is a reason to claim that the cause of wheel surface crumbling could be a chemical composition of the wheel or wheel‐to‐rail hardness ratio. The carried out investigations have revealed that there is no reason to claim that the cause of wheel surface crumbling could be the chemical composition of the wheel or wheel‐to‐rail hardness ratio. First published online: 10 Feb 2011